Meningkatkan Aktivitas, Keterampilan Kerjasama dan Hasil Belajar Siswa Sekolah Dasar Menggunakan Model BAADAP - Suhaimi; Sahryda (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The case encountered in this study is the low activity, student cooperation skills and student learning outcomes in grade IV of SDN Belitung Selatan 9 which is caused by one-way learning, students do not have readiness to learn and low student cooperation and communication. The effort to find a solution to this problem is to apply the BAADAP model in learning. This study aims to describe teacher activities, analyze student activities, student cooperation skills and student learning outcomes. The subject of this study were class IV students of SDN Belitung Selatan 9 Banjarmasin, which totals 9 students. The results of this study show that teacher activity increased with a score of 36 and received very good criteria. Student activity increased to a percentage of 100% with the criteria of all active students. Students' cooperation skills increased to obtain a percentage of 100% with the criteria that all students worked together. Student learning outcomes increased by obtaining 89% student completion.